Analisis Sistem Distribusi Obat di Instalasi Farmasi Rawat Inap Jogja International Hospital - Tri Wijayanti; Sulanto Saleh Danu; Inayati Inayati (Fakultas Farmasi Universitas Setia Budi, 2011)
The research was to determine the drug distribution system used in pharmacy installation Jogja International Hospital and to know the factors that effect the drug distribution system in pharmacy installation Jogja International Hospital. This study used observasional method by case study design. The data was collected by retrospektif and prospektif, with interview and collection data from drug distribution document and the recipe survey in pharmacy installation Jogja International Hospital (JIH). The results showed that drug distribution system used in JIH was UDDS, individual prescription, floorstock and emergency kit. The UDDS used in JIH was not have problem.